C1Q NEPHROPATHY: A MULTIFACETED DISEASE WITH INFREQUENT DIAGNOSIS - Tariq, Naima; Nasir, Humaira; Ahmed, Tahir Aziz; Usman, Mariam; Ahmed, Khawaja Sayeed (Journal of Ayub Medical College Abbottabad, 2019)
Background: C1q nephropathy (C1qN) is a rare glomerulopathy, with a very low prevalence world wide varying from 0.2 to 2.5%. Even though more than three decades have passed since this entity was first explained, still, it remains a dilemma for many due to the rarity of this lesion. This study was carried out principally to determine the clinical presentation, morphologic features and distribution of C1qN in our region based on renal biopsies studied by light microscopy (LM), and immunofluorescence (IF) so that this entity is better understood both by nephrologists and pathologists as no such study has ever been conducted in Pakistan to our knowledge. Methods: It was a cross-sectional study carried out from 1st January 2012 to 30th December 2016 in Histopathology department, Shifa International Hospital. All cases diagnosed as C1q nephropathy were retrieved from the hospital’s computerized database. Their clinical profiles, morphology and immunohistochemical profiles were studied. Results: Over this period a total of 31 cases were diagnosed with C1qN. Mean age of the patients was 32.09±18.66 years. The most common clinical presentation was nephrotic syndrome seen in 22 (71%) patients. The most frequent morphological pattern seen was minimal change disease (MCD) in 13 (41.9%) cases. All cases showed dominant 22 (71%) or codominant 9 (42.9%) mesangial±membranous C1q deposition. No correlation was found (p-value >0.05) between morphological pattern and clinical presentation of the disease or immunofluorescence findings. Conclusion: C1qN is a rare entity which is primarily diagnosed on the basis of immunofluorescence findings with a dominant or codominant fluorescent intensity for C1q. It is recommended that C1qN is sought for preferably with immunofluorescence staining of biopsies for immune reactants, especially for C1q. Studies from this part of the world are strongly recommended to predict clinical outcome and treatment options. Keywords: C1q nephropathy; immunofluorescence; immune reactants; histopathological patterns